PELESTARIAN TARI SIKATUNTUANG DI SANGGAR TARI MANDUGO OMBAK DI KELURAHAN IBUH KECAMATAN PAYAKUMBUH BARAT KOTA PAYAKUMBUH - Shalsa Bila Ivanka; Desfiarni Desfiarni; Darmawati Darmawati (FBS Universitas Negeri Padang, 2018)
Abstract This study aimed to reveal and describe the conservation efforts of the Sikatuntuang Dance at Mandugo Ombak Dance Studio in Ibuh Village, West Payakumbuh Subdistrict, Payakumbuh City. The type of this research was qualitative research with descriptive method inorder to understand a deeper phenomenon. The object of this research wasSkatuntuang Dance in Mandugo Ombak Dance Studio in Ibuh Village, West Payakumbuh Subdistrict, Payakumbuh City. The research instrumentswere the researcher herself whowas assisted by tools such as recording devices, stationery, and a list of interview questions. Data collection techniques in this research were done through library study, observation, interviews and documentation. In this study, the data obtained in the field from the results of observations, interviews, recordings and photographs, then described and arranged in the form of scientific research in the form of an undergraduate thesis. The results showed that the effort to preserve the Sikatuntuang Dance was performed by the Mandugo Ombak Dance Studio through modern teaching methods by means of training and dissemination. The modern way wasdoing regular training of Sikatuntuang Dance at the Mandugo Ombakstudio. Dance practice wasdone three times in a week that were every Friday, Saturday and Sunday at 16.00 to 18.00 P.M. The taught materials, were; a) information, knowledge, introduction, cultural values inculcating from Sikatuntuang Dance, b) the practice of Sikatuntuang Dance.Furthermore, the dissemination was carried out by the Tari Sikatuntuang appearance in various events, such as Tari Sikatuntuang in the Gonjong Limo event in Bandung in 1996, performing at the guest reception in Payakumbuh in 1997, at Padang Cultural Park in 2010, at the opening ceremony of The Singkarak Tour in Jakarta in 2011. In 2015, the Sikatuntuang Dance became one of the traditional art training objects from Japanese visits to the Mandugo Ombak Dance Studio. Moreover, Sikatuntang dance was also performed at the graduation ceremony at Andalas University in 2015 and at wedding events. Keywords: Preservation, Dance, Sikatuntuang, Mandugo Ombak.